Pattern and Stability of the Masticatory Movements in Temporomandibular Disorders Patients - SHIGA, Hiroshi; KOBAYASHI, Yoshinori; MIHASHI, Hiroyuki (Journal of Japanese Society for Mastication Science and Health Promotion, 2001)
In order to clarify the pattern and the stability of masticatory movement in TMD patients, 100 healthy subjects and 100 TMD patients were asked to chew chewing gum and theten cycles beginning with the fifth cycle of mastication were analyzed. The masticatory paths were classified into 9 patterns. The stability of the masticatory movement was determined by calculating the SD/ODs of lateral and vertical components. All results were compared between the two groups. In the healthy subject group the mostly seen pattern was pattern I (the incisal point opened from centric occlusion toward working side and then closed in a convex manner), and patterns I and III (it opened first toward non-working side and then toward working side and closed in a convex manner) together comprised 69.5% of all patterns. In the patient group, pattern III was the mostly observed pattern, and thus showed a different distribution than the healthy subject group. For each pattern the healthy subject group had significantly lower values for the SD/ODs of lateral and vertical components than the patient group. From these results it was concluded that the masticatory movement of TMD patients conspicuously differed from that of healthy subjects, did not possess a specific pattern, came out in various patterns, and regardless of the pattern they were all unstable.